Eunice sensu lato (Annelida: Eunicidae) from Australia: description of seven new species and comments on previously reported species of the genera Eunice, Leodice and Nicidion - Zanol, Joana; Hutchings, Pat A.; Fauchald, Kristian (Zootaxa, 2020)
Species traditionally considered to belong to Eunice are now, also, distributed in two other genera Leodice and Nicidion recently resurrected to reconcile Eunicidae taxonomy with its phylogenetic hypothesis. In Australia, Eunice species have been reported from all seas and sum up to 22 species. In this study, we propose 10 new combinations for traditional Eunice species, which should be moved to Leodice; describe seven new species, four of Eunice and three of Leodice; and comment on species previous recorded from the Australian Coast. Previous records of E. denticulata, E. filamentosa, E. grubei, E. indica, E. longicirris, E. microprion, E. paupera, E. tridentata, E. tubifex and E. vittata from Australia are considered dubious. Eunice tribranchiata, originally described from Australian specimens, is considered here to be an indeterminable species. This study also includes descriptions of Eunice, Leodice and Nicidion as well as key to these genera and their species recorded from Australia.